Superelements Modelling in Flexible Multibody Dynamics - Cardona, Alberto (2000)
We present a new implementation of substructuring methods for flexible multibody analysis. In previous developed formulations, we fixed the local axes of the superelement to one node. In this formulation, the reference frame is floating and close, in some sense, to the body center. The local frame is selected based on the positions of the interface nodes of the superelement, and completely independent of the order in which the nodes of the superelement are given. Therefore, the superelement itself depends only on the nodes positions, and on the mass and stiffness properties, thus allowing a very easy interfacing between the finite element program which computed the superelement and the mechanism analysis program.